LANGUAGE ANALYSIS IN PROMOTION OF BEAUTY PRODUCTS ON SHOPEE IN SKINTIFIC ACCOUNT - Abrar, Virza Ananda; Wahyudi, Athalla Ahmad Dias; Fadiansah, Nailah Ramadhani; Br Ginting, Salsalina Aprilia; Nurhayati, Eni (Dynamic Management Journal, 2024)
This research is entitled "Analysis of Language Variety in the Promotion of Skintific Products at Shopee." The formulation of the problem in this study is to analyze what language styles are used by admins or broadcasters in live broadcasts of skintific product promotions at shopee. This research also describes the persuasive language style used by broadcasters in the promotion of skintific products at shopee. This research uses qualitative description method. The topic of this research is the use of language styles in the promotion of skintific products at shopee. The research instrument used human instrument or was carried out by the researcher himself. Data collection uses recording techniques, listening techniques and note-taking techniques. Qualitative descriptive method is used to analyze the data.